GAMBARAN ERUPSI GIGI DESIDUI BERDASARKAN STATUS GIZI ANAK USIA 6-24 BULAN DI PUSKESMAS BAHU - Sangande, Chandra; Kawengian, Shirley E. S.; S., Anindita P. (Jurnal Biomedik : JBM, 2013)
Abstract: Nutritional status is the health status generated by a balance between the needs and input of nutrients. Children aged 6-24 months have a period of growth and development of deciduous teeth that is very important. Delayed deciduous tooth eruption in children is one impact of malnutrition. This study aimed to reveal deciduous tooth eruptions based on the nutritional status of children aged 6-24 months in Bahu Health Center. This was a descriptive study. Samples were obtained by using a purposive sampling method. Examinations of teeth eruptions were carried out by looking at deciduous teeth that had erupted. Nutritional status was assessed using the indicator of weight for age (W/A). Data of age were calculated using the z-score. Concerning their nutritional status, the results showed that 0.86% of the samples were overweight; 82.60% were well-nourished; 13.04% were less-nourished; and 3.47% suffered from malnutrition. Furthermore, related to their nutritional status, the percentages of the children who experienced complete deciduous teeth eruption were as follow: 100% in overweight, 21.05% in well-nourished, 40.00% in less-nourished, and 0.00% in malnutrition. Conclusion: Most of the children aged 6-24 months in Bahu Health Center were well-nourished. Complete deciduous teeth eruption were found in a single overweight child, a part of well-nourished and less-nourished children, and none in malnutrition children. Keywords: deciduous teeth, tooth eruption, nutritional status. Abstrak: Status gizi ialah status kesehatan yang dihasilkan oleh keseimbangan antara kebutuhan dan asupan nutrisi. Anak berusia 6-24 bulan memiliki masa pertumbuhan dan perkembangan gigi desidui yang sangat penting untuk diperhatikan. Keterlambatan erupsi gigi desidui pada anak merupakan salah satu akibat kekurangan gizi. Penelitian ini bertujuan untuk mengetahui gambaran erupsi gigi desidui berdasarkan status gizi anak usia 6-24 bulan di Puskesmas Bahu. Penelitian ini bersifat deskriptif. Pemilihan sampel dilakukan dengan cara purposive sampling. Pemeriksaan erupsi gigi dilakukan dengan melihat gigi desidui yang telah erupsi. Status gizi dinilai dengan indikator berat badan menurut usia (BB/U), pengambilan data usia, kemudian dihitung dalam nilai z-skor. Hasil penelitian menunjukkan subyek dengan status gizi lebih 0,86%; status gizi baik 82,60%; status gizi kurang 13,04%; dan status gizi buruk 3,47%. Erupsi gigi desidui lengkap ditemukan pada subyek dengan status gizi lebih 100,00%; status gizi baik 21,05%; status gizi kurang 40%; dan status gizi buruk 0,00%. Simpulan: Sebagian besar anak berusia 6-24 bulan di Puskesmas Bahu memiliki status gizi baik. Erupsi gigi desidui lengkap ditemukan pada anak dengan status gizi lebih serta sebagian anak dengan status gizi baik dan kurang, tetapi tidak ditemukan pada anak dengan status gizi buruk. Kata kunci: gigi desidui, erupsi gigi, status gizi.